Cyclopia: A Rare Congenital Malformation - Yadav, Sunil Kumar; Giri, Arun; sah, Vijay Kumar (Journal of Nobel Medical College, 2018)
Cyclopia is a rare and lethal congenital anomaly of the forebrain system, resulting from incomplete cleavage of prosencephalon into right and left hemispheres occurring between the 18th and the 28th day of gestation. Approximately 1.05 in 100,000 births are identified as infants with cyclopia, including stillbirths. Many teratogenic factors are identified as the causative factors for this anomaly which include irregular cholesterol biosynthesis, radiation exposure, viruses, alcohol intake and maternal diabetes. Many authors also suggest genetic etiology of this illness. We report a case of 35 year old lady G7P6L5 with previous history of normal vaginal delivery who presented to us in second stage of labor. She delivered a male baby with a large head, a median single eye and absent nose with intact mouth. The baby died soon after the birth. This case is presented because of its rarity. Early ultrasound diagnostics and proper management of this anomaly must be emphasized most strongly to prevent complication associated with this condition.